(untitled) (Journal of Computational Mathematics, 2021)
In this paper, a new step-size skill for a projection and contraction method^[10] for linear programming is generalized to an iterative method^[22] for solving nonlinear projection equation. For linear programming, our scheme is the same as that of^[10]. For complementarity problem and related problems, we give an improved algorithm by considering the new step-size skill and ALGORITHM B discussed in [22]. Numerical results are provided.